Educação alimentar na escola: treinamento para uso de tecnologia educativa para controle de peso - Cavalcante, Luiza Marques (2018)
The study’s aim was to evaluate a training program conducted with teachers who work in school education to use the serial album “De Olho no Peso”. The specifics were to investigate teachers responses to three of the four levels of assessment of a training proposed by Kirkpatrick (2010a): reaction to training, assessment of learning, knowledge demonstrated before and after the training, as well as post-training behavior, using the serial album by the participants. Evaluative research, developed in two municipal schools of elementary education in Fortaleza, from September to December 2017, after approval by the Research Ethics Committee. Study sites chosen for convenience, with participation of eight teachers who met the inclusion criteria: teaching in classes with students in the age group of 7 to 10 years and attendance at the training workshop. Data collection was performed in three moments: before and after the teacher’s training workshop to use the serial album; by the judges’ analysis of videos made during the application by each teacher of the serial album with schoolchildren and in meeting with the teachers for evaluations’ feedback of its performance. Data analysis was through the attribute system, with four parameters: efficacy, false positive rate, false negative rate and trend. Participants were aged between 30 and 58 years, with a mean age of 39 years, most of them were female, with a training time of 0 to 5 years and 11 to 15 years. There was a prevalence of specialist teachers (62.5%) and a master. In the evaluation of reaction to the training, the items: Evaluation regarding to the subject, Evaluation of the facilitator regarding to the use of support material, Maintenance of a friendly and caring attitude as well as Clarity in the information granted were considered excellent by all teachers. The Facility, Timeline, Facilitator set objectives, Communication of the facilitator with the group, even though they were evaluated by the majority as excellent, received other evaluations (very good and good). In the evaluation of learning, it was observed that the majority of the participants had an acceptable level of knowledge of the subject even before the training, but the number of teachers at this level increased after the training, suggesting a general increase in knowledge and reflecting a positive evaluation of learning. In the evaluation of the overall performance of the teachers by the figure of the album, only the cover’s presentation obtained income below expectations. In the presentations of the scripts, most of the participants obtained a performance evaluation within the expected. It was concluded that the training made possible the qualification of the participating teachers to obtain good performance in the application of the serial album, providing knowledge to use the educational material with the school audience.